Involvement of Hdac3-mediated inhibition of microRNA cluster 17-92 in bronchopulmonary dysplasia development - Wang, Di (Mol Med, 2020)
BACKGROUND: The incidence of bronchopulmonary dysplasia (BPD), a chronic lung disease of newborns, has been paradoxically rising despite medical advances. Histone deacetylase 3 (Hdac3) has been reported to be a crucial regulator in alveologenesis. Hence, this study aims to investigate the mechanism of Hdac3 in the abnormal pulmonary angiogenesis and alveolarization of BPD. METHODS: A hyperoxia-induced BPD model of was developed in newborn mice, and primary lung fibroblasts were isolated from adult mice. Hdac3 was knocked out in vivo and knocked down in vitro, while microRNA (miR)-17 was downregulated in vivo and in vitro to clarify their roles in abnormal pulmonary angiogenesis and alveolarization. Mechanistic investigations were performed on the interplay of Hdac3, miR-17-92 cluster, enhancer of zeste homolog 1 (EZH1), p65 and placental growth factor (Pgf). RESULTS: Hdac3 was involved in abnormal alveolarization and angiogenesis in BPD mice. Further, the expression of the miR-17-92 cluster in BPD mice was downregulated by Hdac3. miR-17 was found to target EZH1, and Hdac3 rescued the inhibited EZH1 expression by miR-17 in lung fibroblasts. Additionally, EZH1 augmented Pgf expression by recruiting p65 thus enhancing the progression of BPD. Hdac3 augmented the recruitment of p65 in the Pgf promoter region through the miR-17/EZH1 axis, thus enhancing the transcription and expression of Pgf, which elicited abnormal angiogenesis and alveolarization of BPD mice. CONCLUSIONS: Altogether, the present study revealed that Hdac3 activated the EZH1-p65-Pgf axis through inhibiting miR-17 in the miR-17-92 cluster, leading to accelerated abnormal pulmonary angiogenesis and alveolarization of BPD mice.